Comunidade de formigas associadas à cochonilha-rosada da cana-de-açúcar em sistemas convencional e orgânico de produção - Cruz, Maiara A.; Feitosa, Rodrigo M.; Peronti, Ana Lúcia B. G.; Martinelli, Nilza M. (Entomological Communications, 2025)
In agroecosystems, the interaction between ants (Hymenoptera: Formicidae) and hemipterans can increase populations of these phytophagous insects, promoting injuries and damage caused by them to crops. The aim of this study was to list the species of ants associated with the mealybug Saccharicoccus sacchari (Cockerell, 1895) (Hemiptera: Pseudococcidae), classifying them according to their presence in the different parts of sugarcane plants. In addition, we verified whether the adopted cultivation system could alter the ant community associated with mealybugs. The experiment was carried out in 2018/19 agricultural harvest, in two sugarcane stands, variety CTC4, in conventional and organic system, both in the municipality of Jardinópolis, SP, Brazil. Ants were collected in the mealybug colonies fixed in different plant structures and sugarcane development stages, including preliminary inspections on the roots of clumps and during plant development, evaluating aerial structures: sprouts, tillers and stalks. Eighteen species of ants were recorded. From these, eight were recorded exclusively in the conventional system, two only in the organic system and eight ant species were common for both systems. It is noteworthy that, for each of the plant structures, clumps and stems, six species of ants occurred exclusively foraging in the mealybug colonies. For sprouting, mealybugs and ants were not observed. We conclude that the cultivation system adopted in the cane field seems to influence ant community associated with S. sacchari. These results can help us to advance in the knowledge about how associated ants can alter the infestation indices of the mealybug in sugarcane fields.